2019
DOI: 10.1002/jbm.b.34333
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and modification of wavy multicomponent vascular grafts with biomimetic mechanical properties, antithrombogenicity, and enhanced endothelial cell affinity

Abstract: A mismatch of mechanical properties and a high rate of thromboses are two critical challenges of creating viable artificial small‐diameter vascular grafts (SDVGs). Herein, we propose a method to fabricate wavy multicomponent vascular grafts (WMVGs) via electrospinning using an assembled rotating collector. The WMVGs consisted of a wavy silk/poly(lactic acid) (PLA) inner layer and a thermoplastic polyurethane (TPU) outer layer, which mimic the structures and properties of collagen and elastin in native blood ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…However, common PUs easily trigger material-induced thrombosis. To enhance their nonthrombogenicity for blood contact implant use, nonthrombogenic moieties were physically or chemically combined with biodegradable PUs, such as phosphorylcholine (PC) [ [173] , [174] , [175] ], sulfobetaine [ 176 , 177 ], sulfate [ [178] , [179] , [180] ], PEG [ 181 ], and antithrombogenic drugs (e.g., clopidogrel, aspirin, and dipyridamole) [ 182 ]. In addition to physical blending and surface modification by nonthrombogenic moieties [ 175 , 177 ], these nonthrombogenic moieties can be covalently incorporated into the PU backbone or grafted onto the polymer chain as pendants.…”
Section: Functional Biodegradable Thermoplastic Polyurethanesmentioning
confidence: 99%
“…However, common PUs easily trigger material-induced thrombosis. To enhance their nonthrombogenicity for blood contact implant use, nonthrombogenic moieties were physically or chemically combined with biodegradable PUs, such as phosphorylcholine (PC) [ [173] , [174] , [175] ], sulfobetaine [ 176 , 177 ], sulfate [ [178] , [179] , [180] ], PEG [ 181 ], and antithrombogenic drugs (e.g., clopidogrel, aspirin, and dipyridamole) [ 182 ]. In addition to physical blending and surface modification by nonthrombogenic moieties [ 175 , 177 ], these nonthrombogenic moieties can be covalently incorporated into the PU backbone or grafted onto the polymer chain as pendants.…”
Section: Functional Biodegradable Thermoplastic Polyurethanesmentioning
confidence: 99%
“…Similarly, Shi and coworkers reported a significant increase in graft endothelialization in vivo in a rat model for electrospun PCL/gelatin loaded with heparin compared to non-loaded ones [60]. Moreover, the heparin surface modification of silk fibroin / PLLA and PLGA / PLLA / PLCL grafts led to an increase in HUVECs attachment, proliferation and migration [61,62]. Also in good agreement, the addition of heparin to modified PTFE grafts was shown to increase HUVECs proliferation compared to grafts without heparin [63].…”
Section: Cell Morphology and Attachmentmentioning
confidence: 96%
“…It has been demonstrated that a coating containing antioxidants on the surface can decrease oxidative degradation [181]. Also, designing a vascular graft based on PU/glycosaminoglycans has shown promising results [182][183][184]. Moreover, PU-nanofibres are nontoxic materials that can provide an environment and substrate for the human umbilical cord vein endothelial cells [184].…”
Section: Pus As Medical Devicesmentioning
confidence: 99%